PENGARUH EKSTRAK KACANG TUNGGAK VIGNA UNGUICULATA TERHADAP PROLIFERASI MATURASI EPITEL PENEBALAN EPITEL SEL LEHER RAHIM SERVIKS: bahasa indonesia - yuliani, ita; Sondakh, Jenny JS; Yulindahwati, Asworoningrum (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Hormone Replacement Therapy estrogen therapy for a long time increases the risk of breast cancer and uterine cancer. It is necessary to find another alternative as a substitute for HRT, namely Cowpea Vigna unguiculata which is considered to be able to increase the proliferation of cervical maturation epithelial thickening epithelium. The design of this study is a true experimental design because there is a treatment, control group and randomization with the type of post test only control group. where testing was performed after the intervention. The intervention carried out was female Wistar strain rats that met the criteria for ovarectomy. There were 3 treatment groups: control rats without treatment, rats were treated with cowpea extract 5 mg KgBW and treated beta estradiol 5g kgBW . This study wanted to determine the effect of cowpea extract Vigna unguiculata on the proliferation of cervical epithelial maturation epithelial thickening in hypoestrogen rats. The research place is the Pharmacology, Physiology and Anatomical Pathology Laboratory, Faculty of Medicine, Brawijaya University, Malang. Research Time The research was carried out for 4 months starting from August 2021 to November 2021. The results of the study using Oneway Anova obtained P Value 0.00 less than Alpha 0.05 so there are differences Treatment outcomes were significantly between groups. Tests of LSD and Mean Plots concluded that cowpea extract 5 mg KgBW gave the most significant difference to the proliferation of maturation epithelium epithelial thickening of cervical cells.